2015
DOI: 10.26879/434
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphism in Quaternary Scelidotheriinae (Mammalia, Xenarthra, Phyllophaga)

Abstract: The contributions concerning possible cases of sexual dimorphisms in fossil and living sloths are scarce. Until now, studies in fossil ground sloth sexual dimorphism have been limited to the subfamilies Megatheriinae (Eremotherium) and Mylodontinae (Paramylodon) from the Pliocene and Pleistocene of South America and North America. Scelidotheriinae constitutes an endemic lineage of ground sloths from South American, with a biochron age ranging the lapse "Friasian"-Lujanian SALMAs (middle Miocene-early Holocene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The discovery of new cave sites and other fossil finds should produce additional evidence on the potential geographic and temporal isolation of P. dominicanus. Evidence for sexual dimorphism in various ground sloths has steadily increased (Cartelle and Bohórquez 1982;Cartelle and De Iuliis 2006;McDonald 2006;Miño-Boilini and Zurita 2015;Boscaini et al 2019;Cartelle et al 2019) and has long been thought to account for the wide variability seen in the Caribbean sloths (Matthew and Paula Couto 1959;). The type locality of Padre Nuestro and nearby La Jeringa each contain the remains of multiple Parocnus individuals (MNI = 5 PN, 12 LJ).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of new cave sites and other fossil finds should produce additional evidence on the potential geographic and temporal isolation of P. dominicanus. Evidence for sexual dimorphism in various ground sloths has steadily increased (Cartelle and Bohórquez 1982;Cartelle and De Iuliis 2006;McDonald 2006;Miño-Boilini and Zurita 2015;Boscaini et al 2019;Cartelle et al 2019) and has long been thought to account for the wide variability seen in the Caribbean sloths (Matthew and Paula Couto 1959;). The type locality of Padre Nuestro and nearby La Jeringa each contain the remains of multiple Parocnus individuals (MNI = 5 PN, 12 LJ).…”
Section: Discussionmentioning
confidence: 99%
“…Fossil sloths do not have unequivocal anatomical features that indicate sexual dimorphism, as in living sloth Bradypus and Choloepus (Figure 4). Nevertheless, some speculations about extinct sloths have been made on the basis of cranial morphology (e.g., Cartelle and Bohórquez, 1982;De Iuliis, 1996;McDonald, 1995McDonald, , 2006Miño-Boilini and Zurita, 2015) and postcranial features (Amson et al, 2015a(Amson et al, , 2015b. For Eremotherium laurillardi, Cartelle and Bohórquez (1982) and De Iuliis (1996), considered that variation in the temporal region of the skull could be explained by sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…We agree that it occurs in different groups of mammals, and add that the ontogenetic age of the specimens can also influence the occurrence and size of such crest (e.g., Carnivora). For scelidotheres, Miño-Boilini and Zurita (2015) suggested that specimens with sagittal crest are males, and specimens lacking sagittal crest are females, but again the ontogenetic stage of the specimens is also a factor to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism has been described for: the megathere, Eremotherium (Cartelle and Bohórques, 1982); the North American mylodont, Paramylodon (McDonald, 2006); and South American scelidothere, Scelidotherium (Miño-Boilino and Zurita, 2015). In these taxa, all skull sizes are comparable in length, but gracile versus robust morphologies in the three genera are attributed to sexual dimorphism.…”
Section: Tarkio Megalonyx Paleobiologymentioning
confidence: 99%